Curriculum Practices and Challenges of English for Da’wah in Islamic Boarding School - Muhajir, R.; Jaelani, Alan; Syhabuddin, Abu (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This study explores the pedagogical integration of English for Da’wah (EFD) in an Islamic boarding school (pesantren) in West Java, Indonesia. Employing a qualitative case study approach, data were collected through document analysis, interviews, focus group discussions, and classroom observations. Findings indicate that EFD is conceptualized as a tool to empower students in global Islamic communication, but its implementation is largely informal, lacking structured curriculum guidelines or teaching materials. While EFD enhances students’ motivation, public speaking skills, and religious identity, challenges such as lexical translation difficulties, limited teacher preparedness, and resource scarcity persist. The study implies the need for contextualized teacher training, collaborative curriculum development, and the creation of pedagogical materials that integrate language instruction with authentic da’wah content.